2016
DOI: 10.1586/14737159.2016.1135739
|View full text |Cite
|
Sign up to set email alerts
|

FindingFMR1mosaicism in Fragile X syndrome

Abstract: OBJETIVE Almost all patients with Fragile X Syndrome (FXS) exhibit a CGG repeat expansion (full mutation) in the Fragile Mental Retardation 1 gene (FMR1). Here, we report five unrelated males with FXS harboring a somatic full mutation/deletion mosaicism. METHODS Mutational profiles were only elucidated by using a combination of molecular approaches (CGG-based PCR, Sanger sequencing, MS-MLPA, Southern blot and mPCR). RESULT Four patients exhibited small deletions encompassing the CGG repeats tract and flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(39 reference statements)
0
16
0
1
Order By: Relevance
“…Generally, a combination of methods might be required to characterize these different facets of the FMR1 expansion mutation [11,93]. …”
Section: Diagnostic Tools For Characterizing the Multiple Moleculamentioning
confidence: 99%
“…Generally, a combination of methods might be required to characterize these different facets of the FMR1 expansion mutation [11,93]. …”
Section: Diagnostic Tools For Characterizing the Multiple Moleculamentioning
confidence: 99%
“…En la literatura, se reporta entre un 12 % y un 41 % de mosaicismo (premutación y mutación completa) en los varones con SFX, 12 que concuerda con lo hallado en nuestro trabajo (el 18,5 %).…”
Section: Discussionunclassified
“…Published studies indicated that FoSTeS/MMBIR is a mitotic event rather than a meiotic one, e.g. somatic mutations associated with the PMP22 and FMR1 genes [ 16 , 31 ]. Therefore, c.532_574del in the ATP7B gene could have occurred through a single FoSTeS/MMBIR event during the mitotic cell division of somatic cells in grandparents or ancestors of the proband (Fig.…”
Section: Discussionmentioning
confidence: 99%